Rising Through the Ranks: The Evolution of the Market for Corporate Executives, 1936–2003 - Frydman, Carola (Management Science, 2019)
I present new stylized facts on the market for managers over the twentieth century, utilizing a novel data set on managerial careers. From the 1930s to the mid-1970s, the level of executive pay, inequality among executives across and within firms, and mobility were low. These patterns have reversed since then. I document that an increase in the importance of general managerial human capital can account for this change. The level of general skills, measured by the type of education and occupational mobility of managers, correlate with higher pay and turnover. Other factors may have also contributed to these changes, but the labor market for managers has likely played an important role. This paper was accepted by Wei Jiang, finance.